Optical measurements of electron spin coherence of nitrogen-vacancy centers in diamond - Andrade, Lucas Nunes Sales de (2021)
Among the possible defects that can occur in diamonds, one that draws attention is the nitrogen-vacancy (NV) center. Studied since the early 90s, in recent years, they became one of the most promising platforms for field applications of quantum technology at room temperature, especially for quantum sensing. They are sensitive to electric and magnetic fields, temperature, and strain, making these nanosensors a versatile platform for many applications. The NV center´s spin state is easy to read and manipulate by optical means, and, most interestingly, it works well at room temperature, which facilitates its use. The great challenge to implement quantum protocols and quantum algorithms is the coherence time of the quantum states. The NV center stands out for having relatively high coherence times at room temperature.This dissertation presents measurements to characterize the electron spin coherence of NV centers in an ultrapure sample of diamond designed for quantum sensing applications. These measurements combine optical e magnetic resonance techniques. For that, a method was implemented using a conventional CCD camera and a clever imaging protocol, making it possible to perform various pulsed microwave experiments on the electron spin, such as Rabi oscillations and Hahn spin-echo, which were used for determining the characteristic relaxation times (T1 and T2). Results show that this system provides at least two readily accessible qubits that can be used in quantum protocols even at room temperature.